Challenges in perioperative fluid management and anticoagulant therapy in a woman with cardio-pulmonary-renal disease diagnosed with preinvasive breast carcinoma - ZQ, Lee; A, Norlia; SM, Syarifah Noor Nazihah; KL, Tan (Penerbit Universiti Kebangsaan Malaysia, 2023)
An elderly woman with preinvasive breast cancer, atrial fibrillation, coronary artery-pulmonary artery fistula, pulmonary hypertension and Stage 4 diabetic nephropathy underwent a mastectomy and sentinel lymph node biopsy. Managing her perioperative fluid balance and anticoagulation treatment were challenging. Having a malignancy, atrial fibrillation plus underhydration will increase her risk of hypercoagulation. However, fluid overload will lead to pulmonary oedema which will decrease her oxygenation further in pulmonary hypertension. Cessation of anticoagulation also increased the risk of hypercoagulation. Anticoagulant therapy increases the risk of a perioperative wound haematoma, which may require another general anaesthesia for identification and arrest of the bleeding source and haematoma evacuation. A haematoma will also increase the risk of surgical site infection; especially as a diabetic. Her anticoagulant therapy (rivoroxaban) was stopped four days preoperatively. Her ejection fraction was 50%, with Grade II diastolic dysfunction and TAPSE 0.6 cm. Her CHA2DS2-VASc Score was 5. Perioperatively, intraarterial cannulation was connected to the FloTrac™ sensor and EV1000™ monitor. Her fluid management was monitored using goal directed (GD) fluid therapy. The patient underwent surgery successfully and her anticoagulant therapy was recommenced 14 days postoperatively.